2019
DOI: 10.1088/1755-1315/268/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Application of biochar coupled with FGD waste for waste management in agriculture improvement

Abstract: Flue gas desulfurization waste (FGD) is one of coal combustion products (CCP) in coal-fired power plants. Mostly, FGD gypsum is applied in cement and wallboard industry. Also, it can be used in agricultural activities for soil amendment but the amount of FGD waste used in this function is still low. Furthermore, biochar has long been used to improve soil fertility. The positive impacts of biochar amendment on soils are that it can increase soil capacity to adsorb plant nutrients, decrease soil bulk density, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…FGD is used in agriculture primarily because it contains a significant number of alkaline oxides, which aid in improving crop growth through acid-base neutralization, soil alteration, and soil modification. 21,22 Yan et al 23 demonstrated that FGD as a calcium source to produce hydroxyapatite (FGD-HAP) can enhance the retention capacity of heavy metals (lead and cadmium) in soil, suggesting that the application of FGD-HAP could diminish the environmental risk of leachable heavy metals to groundwater. FGD was also reported in the field of wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…FGD is used in agriculture primarily because it contains a significant number of alkaline oxides, which aid in improving crop growth through acid-base neutralization, soil alteration, and soil modification. 21,22 Yan et al 23 demonstrated that FGD as a calcium source to produce hydroxyapatite (FGD-HAP) can enhance the retention capacity of heavy metals (lead and cadmium) in soil, suggesting that the application of FGD-HAP could diminish the environmental risk of leachable heavy metals to groundwater. FGD was also reported in the field of wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of gypsum from recycled drywall in soil would allow for the reversal of the harmful effects of road salt on the environment, as it works to rebalance soil pH, reduce loss of essential elements, and increase a plant's tolerance to biotic and abiotic stress factors (Bello et al, 2021;King et al, 2016). Gypsum as a soil amendment is also safe for animals (Sengsingkham et al, 2019). For humans, gypsum is also known to have no toxic effects and is extremely beneficial for agricultural use (United States Department of Agriculture, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Chen et al (2014) specifically tested the toxicity of flue gas desulfurization (FGD) gypsum on earthworms and found no adverse effects on survival, growth, or reproduction (Chen et al, 2014). Similarly, Sengsingkham et al (2019) reported that the use of gypsum-based biochar did not have any negative effects on soil microbial activity, which is an important indicator of soil health (Batool et al, 2015). Furthermore, the nutritional value of gypsum in animal feed has been found to have beneficial effects on nonhuman animal health and productivity as it provides a good source of calcium and sulphur (Cieslar, 2023).…”
Section: Impact Of Gypsum On Non-human Animalsmentioning
confidence: 99%